The home-based automatic self-sanitized waste management system - Mohamed Nor, Noreen Sharina; Abd Latiff, Zatul Iffah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The Home-Based Automatic Self-Sanitized Waste Management System is an innovative solution that automates waste disposal, improves sanitation, and promotes efficient waste segregation. The system utilizes key components such as the ESP32, ultrasonic sensors, servo motors, DHT22 humidity sensor, IR motion sensor, MQ 135 gas sensor and an LCD screen with I2C module, alongside Blynk for remote monitoring and control. The system detects motion using the IR sensor, automatically opening the lid via servo motors for a hands-free experience. The DHT22 sensor determines humidity to classify waste as dry or wet, while the ultrasonic sensor monitors the bin's fill level, displaying real-time data on the LCD screen and sending updates to the Blynk app. Additionally, a built-in self-sanitization mechanism helps maintain cleanliness and reduce odours, enhancing hygiene in home environments. This system stands out for its integration of IoT technology via ESP32 and Blynk, enabling remote monitoring and management, which fosters smarter waste management practices. The project offers significant socio-environmental benefits by encouraging cleaner spaces, reducing manual interaction with waste, and supporting improved public health. Its cost-effective design and user-friendly interface make it highly scalable and promising for commercial applications in both urban and rural settings. By modernizing conventional waste management systems, this solution contributes to smarter, cleaner, and healthier living environments.